Resilience mediates the effect of peer victimization on quality of life in Chongqing adolescents: from a perspective of positive childhood experiences - Deng, Liya; Liu, Yang; Wang, Hong; Yu, Junjie; Liao, Liping (Frontiers in Psychology, 2023)
Background Peer victimization is a harmful experience that contributed to one's psychological problems, physical health deterioration, and so on. Quality of life (QoL) is an important indicator of adolescent health assessment. To identify potential pathways of positive experiences in preventing peer victimization's detrimental effects and then provide intervention ideas for adolescent health, this study was conducted to examine the relationship between peer victimization and QoL in Chongqing adolescents and discover whether resilience plays a mediating role and positive childhood experiences (PCEs) act as a moderating role in the relationship. Methods Data were the first follow-up of a cohort study conducted in four complete middle schools in two districts of Chongqing, China. Self-designed peer victimization items, the Connor–Davidson Resilience Scale, the Adolescent Quality of Life Scale, and the Benevolent Childhood Experiences Scale were used. We investigated the differences and correlations in peer victimization, QoL, and resilience between the two PCEs groups. Mplus version 8.3 was used to analyze the mediating role of resilience and the moderating role of PCEs in peer victimization and QoL. Results Peer victimization, resilience, and QoL differed between the two PCEs groups (P < 0.001). Peer victimization negatively correlated with QoL and resilience, while resilience positively correlated with QoL (P < 0.001). In the models with total QOL as the dependent variable, the indirect effect was −0.431 (8.08% of the total effect) in the low-PCEs group vs. −2.077 (41.97% of the total effect) in the high-PCEs group. In the models with four dimensions of QOL as the dependent variable, the indirect effects ranged from −0.054 to −0.180 (6.07–12.95% of the total effects) in the low-PCEs group and from 0.295 to −0.823 in the high-PCEs group (35.89–68.76% of the total effects). Both total and indirect effects were significant (P < 0.05). In addition, the differences in indirect effects were significant between the two PCEs groups (P < 0.05), while differences in total and direct effects were almost not apparent. Conclusion Resilience partially mediated the effect of peer victimization on QoL in Chongqing adolescents, and PCEs moderated this mediation. Schools, families, and society should focus on resilience intervention and prioritize the enhancement of PCEs for improving adolescent QoL.